Genetic and Functional Characterization of the N-Terminal Region of the Hepatitis C Virus NS2 Protein - de la Fuente, Cynthia (American Society for Microbiology, 2013)
The hepatitis C virus (HCV) NS2 protein has dual roles within the HCV life cycle. While well characterized as an autoprotease that cleaves the NS2/NS3 junction, NS2, primarily via its N-terminal region, is also involved in virion morphogenesis. In order to map the determinants necessary for infectious virus production and gain further insight into the multiple points at which NS2 may impact this process, a detailed mutational analysis of residues spanning amino acids (aa) 1 to 92 was performed. Initial block mutagenesis (5 or 7 amino acid residues) in both bicistronic and monocistronic HCV cell culture-based (HCVcc) genomes revealed that all but two blocks had various levels of impaired infectious virus production. None of these mutations affected RNA replication, indicating that the N-terminal region of NS2 is not required for NS2-3 processing and replicase assembly. Fine mapping identified 29 critical residues that, when mutated, yielded at least a 1 log decrease in infectious virus titers. These mutants were characterized further with respect to release of extracellular HCV RNA and core, intracellular infectivity, thermal stability of virus particles, and NS2 interactions. While the most severely debilitated mutants were impaired early in the assembly process, which is in agreement with previous reports, others targeted later steps of virus production, most notably egress. Thus, in addition to participating in early steps in virion assembly, this comprehensive mutagenesis study suggests yet another role for NS2 in later steps in virus production.